Gait analysis combined with the expression of TGF-β1, TGF-β3 and CREB during Achilles tendon healing in rat - Li-Ming Wu (Elsevier, 2021)
Purpose: To observe the changes of gait behavior and the expression of wound healing factors of transforming growth factor-β1 (TGF-β1), TGF-β3 and cAMP response element binding protein-1 (CREB-1) during the healing of Achilles tendon in a rat model, and to investigate whether gait analysis can be used to evaluate the tendon healing. Methods: Achilles tendon of 40 healthy male Sprague-Dawley rats were transected and sutured to establish the Achilles tendon injury (ATI) model. They were randomly divided into 4 groups based on the observational time point at 1, 2, 4 and 6 weeks after injury (n = 10 for each group). Before modeling, 9 rats were randomly selected for CatWalk gait analysis, which contained step cycle, single stance time and average speed. Data were recorded as the normal controls. After then, ATI models were established in the left hind limbs of the all 40 rats (ATI group), while the right hind limbs were only cut and sutured without injury of the Achilles tendon (sham operation group). At 1, 2, 4 and 6 weeks after injury, the gait behavior of the corresponding group of rats (n = 9) as observed and recorded by CatWalk platform. After then, the rats were sacrificed and Achilles tendon of both limbs was harvested. The tendon healing was observed by gross anatomy and histological examination, and the protein and mRNA expression of TGF-β1, TGF-β3, CREB-1 were observed by immunohistochemistry and qPCR. The results of tendon gross grading were analyzed by Wilcoxon rank sum test, and other data were analyzed by one-way analysis of variance among multiple groups. Results: Compared with normal controls, all gait indexes (step cycle, single stance time and average speed) were greatly affected following ATI, which however improved with time. The step cycle was significantly lower at 1, 2 and 4 weeks after ATI (compared with normal controls, all p < 0.05), but almost returned to the normal level at 6 weeks ((0.694 ± 0.102) vs. (0.503 ± 0.094) s, p > 0.05). The single stance time of the ATI group was significantly shorter at 1 and 2 weeks after operation ((0.078 ± 0.010) s at 1 week, (0.078 ± 0.020) s at 2 weeks, all p < 0.001) and revealed no significant difference at 4 weeks (p = 0.120). The average speed of ATI group at 1, 2, 4, 6 weeks was significantly lower than that in the normal control group (all p < 0.001).Gross observation showed that the grade of local scar adhesion in ATI group increased significantly at 2, 4 and 6 weeks, compared with the sham operation group (all p < 0.001). Extensive adhesion was formed at 6 weeks after ATI. The results of HE staining showed that the number of fibroblast increased gradually and arranged more orderly in ATI group at 1, 2 and 4 weeks (all p < 0.001), and decreased at 6 weeks, but it was still significantly higher than that of the sham operation group (p < 0.001). Immunohistochemistry showed that the positive expression of TGF-β1, TGF-β3, CREB-1 in ATI group was higher than that in the sham operation group at 4 time points (all p < 0.05), which reached the peak at 2 weeks after operation and decreased at 4 weeks (p = 0.002, p < 0.001, p = 0.041, respectively). The results of qPCR suggested that the mRNA expression of TGF-β1, TGF-β3, CREB-1 in ATI group was higher than that in the sham operation group at all-time points (all p < 0.05), which reached the peak at 2 weeks after operation, decreased at 4 weeks, and significantly decreased at 6 weeks (all p < 0.001). Conclusion: Gait behavior indexes are associated with Achilles tendon healing. The study gives an insight of TGF-β1, TGF-β3, CREB-1 changes in the coursing of Achilles tendon healing and these cytokines may be able to be used to regulate the Achilles tendon healing.